Brand Loyalty : Study On Malaysian Female Perspective - Chong, Lydia Li Ting (2006)
This study is to focus on the Malaysian Females and a detail study on the three selected states that are Johor, Sarawak and Selangor. The study found that there are differences in the selection of a brand name. The level of satisfaction will affect the loyalty of the female customers and through Customer Relationship Management is to study and understand the customer's needs and wants.